Organizational Citizenship Behavior on Nurses: The Role of Organizational Commitment and Job Satisfaction - Abdhy Aulia Adnans, Eka Danta Jaya Ginting, Silvana, Achmad Rizal (International Journal of Advanced Science and Technology, 2020)
Every organization must have a strategy in achieving success, like a hospital. In this case, human resources have a significant role. The organizational citizenship behavior of each employee will help the hospital to achieve its goals. Organizational citizenship behavior can be created if employees are committed to the company so that they will contribute significantly to work. Besides, job satisfaction felt by employees also participates in influencing organizational citizenship behavior displayed by employees. This study aims to determine the effect of organizational commitment and job satisfaction on organizational citizenship behavior displayed by nurses at the Hospital. This study involved 160 nurses at Hospital. The measuring instruments used in this study were the scale of organizational citizenship behavior, organizational commitment, and job satisfaction. The results of the simple regression analysis show that organizational commitment and job satisfaction together affect organizational citizenship behavior. Organizational commitment and job satisfaction make a positive contribution to organizational citizenship behavior. This research implies that hospitals can improve organizational citizenship behavior that will be displayed by nurses by paying attention to things that can make nurses feel satisfied in the work environment and by training that can increase the commitment of nurses.